2020
DOI: 10.4094/chnr.2020.26.3.385
|View full text |Cite
|
Sign up to set email alerts
|

Gambling Subgroups among Korean Out-of-school Adolescents

Abstract: Purpose: The number of Korean adolescents engaging in gambling is increasing, especially among out-of-school adolescents. This study aimed to identify patterns of gambling activities and factors related to specific subgroups of out-of-school adolescent gambling activities.Methods: This descriptive study analyzed secondary data from the 2015 Korea Youth Gambling Problem Survey, including 1,200 out-of-school adolescents. Latent class analysis was conducted to identify patterns of gambling activities. The factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…Young males were reported to have both greater participation in gambling and gambling problems than females [10,20,21,23,25,[30][31][32][33][34][35][36]46,[48][49][50][51][52][53][54]. Indeed, being male was reported to increase the odds of being a moderate to high risk problem gambler by 25 [19] to 37 times [44].…”
Section: Young Malesmentioning
confidence: 99%
See 3 more Smart Citations
“…Young males were reported to have both greater participation in gambling and gambling problems than females [10,20,21,23,25,[30][31][32][33][34][35][36]46,[48][49][50][51][52][53][54]. Indeed, being male was reported to increase the odds of being a moderate to high risk problem gambler by 25 [19] to 37 times [44].…”
Section: Young Malesmentioning
confidence: 99%
“…Most studies observed whether young people had ever participated in gambling or had gambled within the previous 12 months, and reported the prevalence of problem gambling, which was typically reported as low or moderate risk of problem gambling, or problem gambling. Lifetime participation in gambling rates ranged between 42.1% [10] and 89.9% [20], with the majority of studies that examined gambling participation reporting that around a third or more of adolescents or young adults confirmed that they had gambled at least once in their lifetime [10,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Gambling participation rates during the past 12 months ranged between 18.6% [38] to 85% [23].…”
Section: Gambling Participation and Problem Gamblingmentioning
confidence: 99%
See 2 more Smart Citations
“…We recruited a sample of 869 adolescents (mean age 15.18 years [SD = 1.17], 52.6% males) attending four public high schools in the province of Huelva (Spain). Huelva is a province located in the southwestern of Spain, with a total of 92 public high schools and an estimation of roughly 31,000 students (INE, 2021). The sample was selected based on geographic and social representativeness.…”
Section: Participants and Proceduresmentioning
confidence: 99%